Economic Inequality and Healthcare Access: A Study of the Effectiveness of Indonesia’s National Health Insurance Scheme (BPJS) in Addressing Health Disparities (Indonesian Health Justice Review, 2025)
Indonesia’s National Health Insurance (BPJS) system was introduced to promote universal healthcare coverage and address economic disparities in healthcare access. This paper critically evaluates the effectiveness of BPJS in mitigating healthcare inequalities, particularly for low-income and vulnerable populations. By analyzing BPJS data, conducting surveys, and interviewing healthcare providers and beneficiaries, the study assesses the extent to which the program has improved access to healthcare services for lower-income Indonesians. Despite significant strides in expanding coverage, the research identifies several persistent challenges, including financial barriers to accessing quality care, long waiting times, and underfunded public healthcare facilities. The study also explores how BPJS’s funding model, based on premiums paid by workers, may disproportionately impact the poor, leading to gaps in coverage and affordability. The paper argues that while BPJS has increased healthcare access in some areas, it has not fully addressed the economic inequality that affects the poorest populations. Recommendations include revising the BPJS premium structure, increasing funding for public healthcare facilities, and improving the quality of services provided to ensure equitable access to healthcare for all segments of Indonesian society.